Peninjauan Hubungan Pengetahuan, Sikap, dan Tindakan Pencegahan Terhadap Penyakit Rabies di Soppeng - Murtini; Kassaming; Husnul Khotimah Rustam; Sudirman (Universitas Duta Bangsa Surakarta, 2022)
Rabies is a deadly disease that is transmitted from animals to humans and attacks the central nervous system. Dogs are the main source of transmission of rabies to humans through saliva containing the rabies virus. The purpose of the study was to determine the relationship between knowledge, attitudes and preventive actions against rabies in the UPTD Work Area of ​​Tanjonge Health Center, Soppeng Regency. This study used an analytic observational method with a cross sectional approach. Many samples used, namely 32 samples, data obtained by interviewing respondents using questionnaires that have been structured in a structured manner. The results showed that the proportion of the relationship between knowledge and rabies showed that a good knowledge of rabies with symptoms of anxiety was 59%. Meanwhile, rabies with wound pain is 15%. The results of the Chi-Square bivariate analysis on the knowledge variable are p-value = 0.028, attitude variable p-value = 0.13 and the precautionary variable p-value = 0.38. Judging from the p-value that knowledge has a significant relationship with rabies, while attitudes and precautions do not have a significant relationship with rabies. It is hoped that other research can be conducted with variables not examined in this study. For the UPTD of the Tanjonge Health Center, conducting promotive and preventive efforts to the community by increasing public knowledge through counseling about rabies.